STRUKTUR ARGUMEN DALAM WACANA KARYA TULIS ILMIAH MAHASISWA - Ardianto, Ardianto (LITERA, 2015)
This study aims to describe argument structures based on types of complexity and conclusion drawing in students' academic writing discourse. It employed the qualitative descriptive approach using the communication content analysis method. The data sources were undergraduate theses written by students of the Department of Tarbiyah, STAIN Manado. The results of the study are as follows. First, the argument structures based on types of complexity comprise a simple argument structure and a complex argument structure. The complex argument structure consists of an adjacent argument structure and a multi-layer argument structure. Second, the argument structures based on conclusion drawing consist of an inductive argument structure and a deductive argument structure.